2014
DOI: 10.1186/s12052-014-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Gifted students’ perceptions of their acceptance of evolution, changes in acceptance, and factors involved therein

Abstract: Background: Few reports have tracked changes in the levels of acceptance of evolution among high school students, and there have apparently been no studies exploring the levels of acceptance of evolution among gifted high school students in transition to post-secondary education. And, although many have measured acceptance of evolution via various instruments, there has been little information regarding what students consider to be important factors affecting changes in their positions of acceptance or rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…This link was also found in an undergraduate sample (Carter and Wiles 2014). Other studies (Heddy and Nadelson 2013;Mazur 2004;Wiles 2014) have found more generally that higher education levels lead to greater acceptance of evolution. Barone et al (2014) found a significant correlation between knowledge of evolutionary terms and acceptance of evolution among visitors to a natural history museum.…”
Section: Introductionsupporting
confidence: 52%
“…This link was also found in an undergraduate sample (Carter and Wiles 2014). Other studies (Heddy and Nadelson 2013;Mazur 2004;Wiles 2014) have found more generally that higher education levels lead to greater acceptance of evolution. Barone et al (2014) found a significant correlation between knowledge of evolutionary terms and acceptance of evolution among visitors to a natural history museum.…”
Section: Introductionsupporting
confidence: 52%
“…This is a logical and expected result (Cotner et al 2009;Kim and Nehm 2011;Moore et al 2011). In general, students respond well (via increase in knowledge) when evidence of evolutionary theory is provided and specific misconceptions are targeted (Wiles 2014;Moore et al 2011). Obviously educating students on evolution will improve their understanding of it, but some studies show this is only true for the least religious students (Moore et al 2011;Kahan 2015;Rissler et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…The multiple mechanisms of evolution such as natural selection, stochastic events, and geographical isolation, involve intellectually challenging concepts such as deep time, probability and situations of uncertainty, speciation, and the nature of science (Gould 2002;Scharmann and Harris 1992). Because of the complexity of biological evolution, people are likely to be challenged to understand the process (Moore and Cotner 2009;Nadelson and Southerland 2010), which may influence their levels of evolution acceptance (Nadelson and Sinatra 2009;Wiles 2014;Wiles and Alters 2011).…”
Section: Evolution Acceptancementioning
confidence: 99%